The co-movement of selective conventional and Islamic stock indices: is there any impact on shariah compliant equity investment in China? - Saiti, Buerhan; Masih, Mansur (EconJournals, 2016)
This paper investigates the dynamic causal linkages in the daily returns among four conventional and three Shariah compliant indices (such as, Financial Times Stock Exchange Shariah China Index, Asia Shariah Index, Malaysia EMAS Shariah Index, China Shanghai Stock Exchange [SSE] Composite Index, Hang Seng Index, Nikkei 225 and KOSPI) in Asia region through the application of the standard time series techniques. Essentially, the purpose of this research is to identify the extent of infl uence of conventional and Islamic, regional and international equity markets on Shariah compliant equity investment in China. Our study is focused on investigating the following empirical questions: (i) Which indices do the Shariah China Index commove with? (ii) Which indices is the Shariah China Index Granger-causally related with? and (iii) Which major stock index was driving the selective conventional and Shariah compliant stock indices? Our fi ndings tend to suggest: (i) The Shariah China Index appears to have a theoretical and long-run comovement with all the select conventional and Shariah compliant stock indices (as evidenced in the Cointegration and LRSM tests) (ii) The Shariah China Index is Granger-caused by all the conventional and Shariah compliant stock indices (as evidenced in the vector error correction modelling tests) (iii) Finally, what stands out is the leadership of the China conventional SSE market followed by the Malaysia Shariah market in driving all indices including the Shariah China Index (as evidenced in the VDCs tests).